The Improvement of 5 kV - Output Boost Converter Using Interleaving Method - Azlan, A.F.M. (Institute of Electrical and Electronics Engineers Inc., 2021)
Recently, the development of DC long transmission line has been reconsidered as it emits less power loss as compared to AC power transmission line. The reason is because, the implementation of non-isolated converter in the system could omit the uses of transformer that contributes to the conversion loss. Besides, interleaving method is incorporated in the converter as a very high DC voltage is needed to be transmitted along the DC long transmission line. By applying such method, the output voltage ripple and output current ripple can be reduced. In this paper, modelling and simulating is done in MATLAB/Simulink for both interleaved and conventional boost converter with same switching frequency at 50 kHz. The results and analysis of both converters are based on Continuous Current Mode (CCM). The improvement of boost converter by using interleaving method can get a better voltage gain, reduced output voltage ripple as well as reduced output current ripple. Â© 2021 IEEE.